ENDOTHELIAL DYSFUNCTION IN PATIENTS WITH CORONARY HEART DISEASE AND TYPE 2 DIABETES MELLITUS - M. M. Petina; G. N. Gorokhovskaya; A. I. Martynov (Российский кардиологический журнал)
Endothelial dysfunction is one of the earliest stages in atherosclerosis development among patients with diabetes mellitus (DM). At the moment, cardiovascular disease (coronary atherosclerosis complications and coronary heart disease, CHD) is the leading cause of disability and mortality in patients with Type 2 DM (DM-2). This justifies the need for а thorough pathogenetic investigation of diabetic microangiopathy, endothelial function, and endothelial dysfunction role in the development of CHD in DM-2 patients. The study included 35 patients with CHD and DM-2; 35 patients with DM-2 and no CHD; 15 healthy volunteers, comparable by age and sex with DM-2 patients (control group). Endothelium-dependent vasodilatation, anti-thrombogenic activity of vascular wall, and hemostasis parameters were assessed in all participants. In patients with CHD and DM-2, functional endothelial activity was substantially decreased, including such parameters as flow-dependent vasodilatation, anti-coagulant, anti-aggregant, and anti-fibrinolytic activity. These disturbances were progressing over the clinical course of the disease and directly correlated with the disease severity.